Green Accounting Sebagai Strategi Keuangan Berkelanjutan Menuju Net Zero Emission 2060 Pada PT. Bank Mandiri Terdaftar Di BEI - Al Iksan Inggo; Marten Puyo; Kartini Muslimin (JSAP: Journal Syariah and Accounting Public, 2026)
Abstract: Sustainable finance strategies integrate the principles of economic efficiency, social justice, and environmental sustainability into every financial decision. This study aims to analyze the implementation of green accounting and sustainable finance strategies at PT Bank Mandiri (Persero) Tbk in support of achieving the 2060 Net Zero Emissions (NZE) target. The study employs a descriptive qualitative approach using document analysis based on Bank Mandiri’s 2024 Sustainability Report, which is further examined in accordance with Global Reporting Initiative (GRI) standards and Financial Services Authority Regulation (POJK) No. 51/POJK.03/2017. The results of the study indicate that Bank Mandiri has implemented green accounting principles in an integrated manner through the recognition, measurement, and disclosure of environmental costs and impacts, particularly regarding greenhouse gas emissions management, energy efficiency, and transparency in sustainability reporting. Sustainable finance strategies are implemented through the application of the Sustainable Finance Framework and the Transition Finance Framework, the development of green financing products, and the integration of environmental, social, and governance (ESG) aspects into risk management and financing policies. In addition, strengthening human resource capacity through training and ESG literacy contributes to the internalization of sustainability values throughout the organization. Nevertheless, this study identified key challenges, including the complexity of measuring indirect emissions (financed emissions) and the need to foster a culture of sustainability across the board. Overall, this study concludes that the implementation of green accounting plays a crucial role in enhancing accountability, transparency, and the effectiveness of sustainable finance, as well as supporting the banking sector’s transition toward a low-carbon economy. Keywords: Green Accounting, Sustainable Finance Strategies, Net-Zero Emissions Strategi keuangan berkelanjutan mengintegrasikan prinsip efisiensi ekonomi, keadilan sosial, dan kelestarian lingkungan dalam setiap keputusan keuangan Penelitian ini bertujuan untuk menganalisis penerapan green accounting serta strategi keuangan berkelanjutan pada PT Bank Mandiri (Persero) Tbk dalam mendukung pencapaian target Net Zero Emission (NZE) 2060. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode analisis melalui dokumen yang menggambarkan Laporan Keberlanjutan Bank Mandiri Tahun 2024, dan selanjutnya ditelaah berdasarkan standar Global Reporting Initiative (GRI) dan Peraturan Otoritas Jasa Keuangan (POJK) No. 51/POJK.03/2017. Hasil penelitian menunjukkan bahwa Bank Mandiri telah mengimplementasikan prinsip green accounting secara terintegrasi melalui pengakuan, pengukuran, dan pengungkapan biaya serta dampak lingkungan, khususnya terkait pengelolaan emisi gas rumah kaca, efisiensi energi, dan transparansi pelaporan keberlanjutan. Strategi keuangan berkelanjutan diwujudkan melalui penerapan Sustainable Finance Framework dan Transition Finance Framework, pengembangan produk pembiayaan hijau, serta integrasi aspek lingkungan, sosial, dan tata kelola (ESG) dalam manajemen risiko dan kebijakan pembiayaan. Selain itu, penguatan kapasitas sumber daya manusia melalui pelatihan dan literasi LST berkontribusi dalam internalisasi nilai keberlanjutan di seluruh organisasi. Meskipun demikian, penelitian ini menemukan tantangan utama berupa kompleksitas pengukuran emisi tidak langsung (financed emissions) dan kebutuhan penguatan budaya keberlanjutan secara merata. Secara keseluruhan, penelitian ini menyimpulkan bahwa penerapan green accounting berperan penting dalam meningkatkan akuntabilitas, transparansi, dan efektivitas keuangan berkelanjutan, serta mendukung transformasi perbankan menuju ekonomi rendah karbon. Kata kunci: Green Accounting, Strategi Keuangan Berkelanjutan, Net Zero Emission.